Flood Assessment Study in The City of Tangerang, West Java - Acep Hidayat (IPTEK Journal of Proceedings Series, 2017)
Tangerang city is a region which has a relatively flat and inclined contour-shaped basin so that in some areas when the rains come will experience flooding. The cause of the flooding is necessary to identify the field. From the results obtained that the identification of flood discharge for the region amounted to 29.91 m³ / s with 1.65 km².Dari watershed area of this discharge can only be accommodated by the existing drainage network is only 5 m³ / sec so that the excess is what makes this region flood. For excess of 24.91 m³ / s is done by creating a polder or ponds so that these advantages can be accommodated. Polder or ponds that can accommodate this excess area of 6.3 hectares with a depth of 4 meters. In addition to planning embung / Polder required also increase drainage infrastructure sehigga can flow smoothly.